The impacts of roll-on/roll-off transport system in the Philippines - Kris A. Francisco (Philippine Institute for Development Studies (PIDS), 2017)
It is well recognized in the literature that a country's transport system plays a central role in its development. This paper shows the economic impacts of improvements in the transport system by studying the experience of the Philippines with the roll-on/roll-off (Ro-Ro) policy that promotes the use of Ro-Ro ferry terminal system. Using difference-in-difference strategies in analyzing agricultural household income and children's education, the study finds that the operation of Ro-Ro ports largely benefited the households living near the Ro-Ro ports. More specifically, estimates suggest that agricultural households gained higher income from the operation of these ports because both agriculture- and nonagriculture-related activities were stimulated. Results also imply the boost in nonagriculture-related activities in the islands where the Ro-Ro ports are located. Meanwhile, analysis on children's education reveals an increase in school attendance of males and females in municipalities near the Ro-Ro ports. The study also confirms that there was an increase in family income in these areas, thereby suggesting the increased capacity of households to send children to school. As a whole, the study demonstrates some examples of short- and long-run impacts of improving a country's transport system. Likewise, it highlights the importance of an efficient and affordable transport system in an archipelagic country like the Philippines.
Keywords: 330; Transport system; Roll-on/Roll-off policy; Agriculture; Education